Spatial Resilience of Local Places: A comparative study on Beijing’s breakfast service before and after Covid-19 - Wu Jingfen; Sheng Qiang (Lodz University of Technology Press, 2023)
The distribution of breakfast services under the impact of COVID-19 provides an ideal case for studying the supporting role of urban space on self-organized commerce. Based on the large-scale, multi-type and high-precision field survey of breakfast services in the central urban area of Beijing in 2019 and 2020, this paper analyzes the distribution pattern of breakfast services by using topological spatial accessibility based on spatial syntax, combined with the work-housing and commuting density data obtained by mobile signaling. Statistics showed that after the epidemic, the total amount of breakfast decreased and the distribution imbalance was further aggravated but the location of the gathering center was stable. Breakfast services on high topological accessibility streets are more likely to survive. Regression analysis showed that residential density had a greater effect than working density except for breakfast in the supermarket. Streets with high topological accessibility and close to subway stations have a stable supporting effect on the survival of breakfast services.
Keywords: breakfast service; urban vitality; Covid 19; space syntax; sell phone data; serwis śniadaniowy; witalność miejska; składnia przestrzeni; sprzedaż danych telefonicznych